The changing landscape of Indian agriculture - Gulati, Ashok; Ganguly, Kavery (Wiley, 2010)
In tracking the revolutionary changes in the Indian agricultural sector, it is quite clear that technology, institutions, and markets have had a very important role to play. Of course, the public sector played a pivotal and catalytic role when India ushered in the Green Revolution in late 1960s and early 1970s. The public sector imported new seeds, organized their distribution and demonstration, and provided price and market support, all “not‐for‐profit.” The cooperative sector, supported and facilitated by the government, again with the spirit of “not‐for‐profit,” helped bring in the White Revolution in milk through Operation Flood in 1970s and 1980s. This spirit is now being gradually replaced by “for‐profit” objective driven by the private sector, as is demonstrated in the revolutionary changes brought about by the introduction of Bacillus thuringiensis technology in the cotton sector during 2002–2007. On top of this, the corporate sector is also changing the complexion of the Indian agrisystem through notable changes in organized food processing and retailing. This change in spirit from “not‐for‐profit” to “for‐profit” in the growth process of Indian agriculture has significant implications for the concept of CISS, i.e., competitiveness, inclusiveness, sustainability, and scalability, which needs to be studied carefully and in detail. Accordingly, this article traces some of these dynamic changes and their likely implications.